Physical Activity for Public Health in the 21st Century - Salvo, Deborah; Crochemore-Silva, Inacio; Wendt, Andrea; Tarp, Jakob; Shiroma, Eric J; Simpson, Richard J; Lee, I-Min; Ekelund, Ulf; Cerin, Ester; Keita, Youssouf; Bauman, Adrian; Hallal, Pedro C; et al. (Nature Research, 2026)
With over 5 million attributed deaths per year, physical inactivity is a major global public health issue. Although the importance of physical activity is well recognized within the scope of obesity and cardiometabolic disease prevention and control, its broader benefits for the health of individuals and societies are yet to be fully harnessed. Furthermore, the role of active leisure, active transport and active labor-primary domains of physical activity-in supporting or hindering social and health equity has been largely overlooked. Here we (1) used a health equity lens to describe global domain-specific physical activity inequalities through an analysis of World Health Organization STEPwise approach to NCD risk factor surveillance (WHO STEPS) data from 68 countries; (2) summarized evidence linking physical activity with health outcomes beyond cardiometabolic disease, including immunity and infectious disease, depression and cancer; and (3) developed a new model reconceptualizing physical activity to better respond to 21st-century public health challenges. Our global, intersectional analysis of gender and socioeconomic physical activity inequalities revealed a 40-percentage-point gap in active leisure-the only domain consistently driven by choice-between historically privileged groups (wealthy men in high-income countries) and historically disadvantaged ones (poor women in low-income countries). Robust evidence supports the benefits of physical activity for immunity and infectious disease, depression and cancer. Our reconceptualized model recognizes the influence of social identities, norms, policies and structures on physical activity for health and wellbeing and emphasizes the urgent need to develop and roll out policies and programs that disseminate and harness the full benefits of physical activity for human, societal and planetary health.
Keywords: 32 Biomedical and Clinical Sciences; 4206 Public Health; 42 Health Sciences; 3202 Clinical Sciences; Prevention; Social Determinants of Health; Health Disparities; Behavioral and Social Science; Health Disparities and Racial or Ethnic Minority Health Research; Physical Activity; Basic Behavioral and Social Science; Clinical Research; 3.1 Primary prevention interventions to modify behaviours or promote wellbeing; Cancer; Cardiovascular; 3 Good Health and Well Being; 10 Reduced Inequalities; 11 Medical and Health Sciences; Immunology; 32 Biomedical and clinical sciences; 42 Health sciences; Humans; Exercise; Public Health; Female; Male; Socioeconomic Factors; Global Health; Risk Factors; World Health Organization; Humans; Exercise; Risk Factors; Public Health; Socioeconomic Factors; World Health Organization; Female; Male; Global Health; Humans; Exercise; Public Health; Female; Male; Socioeconomic Factors; Global Health; Risk Factors; World Health Organization